Environment Law-Based Rural Tourism Regulations in Bali - Budiartha, I Nyoman Putu; Sugiartha, I Nyoman Gede; Dewi, A.A. Sagung Laksmi (Warmadewa Press, 2022)
An environmental management made for the purpose of obtaining clean and healthy atmosphere is a human right of every Indonesian citizen as mandated in Article 28H of the 1945 Constitution of the Republic of Indonesia. Poor environmental management contributes to the deterioration of the quality of the environment. Therefore, it is necessary to increase its protection and management. Managing the environment for the benefit of rural tourism development is the responsibility of community members who are business actors and the government. The function of the government together with business actors and the community in preserving the environment is a function of public services to ensure that every resident obtains a good and healthy environment. Thus, in the event that business actors or the public fail to carry out their obligations and which are not in accordance with the nature of environmental conservation, the government may hold the business actors and the public accountable, who in carrying out their activities, are negligent in preserving the environment, either administratively, civilly or criminally. Likewise, in the event that the government is proven to have taken actions that are not in line with the provisions of the law on environmental protection and management, they can be held legally liable. This study is qualified as empirical legal research, with the application of several types of approaches, such as a field-based approach, a statutory approach, a conceptual approach, a comparative approach, a case approach, and a cultural approach based on local community wisdom. The results of the study show that environmental management is an effort to carry out responsibilities that are massively difficult, resulting in a decrease in the quality of the environment that is becoming increasingly real. Therefore, in the event that pollution and environmental destruction occur, the perpetrators can be held accountable both in civil law and criminal law. However, in a context like Bali, regulations integrating the values ​​that develop in society in protecting and preserving the environment are an ideal form to protect and manage the environment in a rational way to realize sustainable tourism development.